UTILITIES OF BIPOLAR PROSTHESIS IN INTRACAPSULAR FRACTURE NECK OF FEMUR - DR M.VINODKUMAR; DR.P.RAMACHANDRA RAO (International Journal of Pharma and Bio Sciences, 2014)
Hip fractures are devastating injuries that commonly affects the elderly and have a tremendous impact on both the health care system and society in general. Hemi arthroplasty with bipolar prosthesis offers advantages of rapid return to function with pain free hip. In addition; it is cheaper and easier to perform than total hip arthroplasty and also preserves the original acetabulum and reduces the complications of uni polar arthroplasties and better joint function. It is also used as a salvage for failed total hip and unipolar arthroplasties where earlier alternative was excision arthroplastyIn this study of 25 cases of displaced intracapsular fracture of the neck of femur, neglected intracapsular fractures of more than 3-4 weeks old and patients less than 60 yrs of age, non union of intracapsular fractures of neck of femur and intracapsular fractures of neck of femur with early avascular necrosis.In our study of 25 patients, 18 had excellent results with Harris hip scores more than 90, 6 patients had good result with Harris hip score between 80 and 90 and 1 patient had a fair result.Elderly patients and physiologically younger patients with displaced intracapsular fractures of the neck of femur, treated with bipolar hip prosthesis offer excellent, painless mobility , with low rate of complications, component survival is long and pre injury functional status restored